Evaluation of Different Bio-control Agents and Fungicides against Alternaria brassicae Causing Alternaria Blight of Mustard - , Hemalatha S; , Sibte Sayyeda; , Vaibhav Pratap Singh; , Devesh Pathak; , R. U. Khan (Archives of Current Research International, 2025)
The present investigation was carried out in vitro to check the efficacy of different bio-control agents and fungicides to inhibit the growth of Alternaria brassicae causing Alternaria blight of mustard. All the tested bio-control agents and fungicides significantly inhibited the growth of pathogen compared to control. Of all bio-control agents, Trichoderma harzianum (77.04%) was found to be highly effective in mycelial growth inhibition of A. brassicae followed by T. viride (67.77%). However, least inhibition (60.00%) was observed with T. hamatum. Among the tested fungicides, Propiconazole, Hexaconazole and Azoxystrobin were found to be most effective at all four tested concentrations of 50, 100, 150 and 200 ppm, thereby causing complete growth inhibition. While as, Propineb was found to be least effective at all concentrations in comparison to other fungicides.